Comparison of live birth rates after IVF–embryo transfer with and without preimplantation genetic testing for aneuploidies. Issue 6 (December 2021) - Sadecki, Emily; Rust, Laura; Walker, David L.; Fredrickson, Jolene R.; Krenik, Anthony; Kim, Tana; Weaver, Amy L.; Zhao, Yulian
Abstract: Research question: Does the use of preimplantation genetic testing for aneuploidies (PGT-A) result in higher live birth rates when compared with both fresh and frozen embryo transfers (FET) not utilizing PGT-A? Design: Retrospective cohort study at a single tertiary centre using inverse probability of treatment weighting (IPTW) to adjust for differences in baseline characteristics between groups. Results: A total of 107 FET using PGT-A from 74 patients, along with 321 fresh and 286 FET not using PGT-A from 381 patients met the inclusion criteria for this study. In the IPTW-adjusted analysis of transfer-level data, PGT-A transfers resulted in a significantly higher live birth rate when compared with both non-PGT-A fresh (49.5% versus 38.6%, P  = 0.036) and FET (50.6% versus 35.8%, P  = 0.016). When data were analysed per retrieval level, the live birth rate was similar and acceptably high with or without PGT-A (63.7% versus 52.3%, P  = 0.09). Conclusion: When comparing PGT-A to non-PGT-A fresh and FET, PGT-A embryo transfers have a significantly higher live birth rate. However, this difference did not persist at a per-retrieval level. Further investigation is needed to understand in what scenarios PGT-A has clinical significance and whether differences in the number of available embryos for transfer negates the benefit of PGT-A.